2018
DOI: 10.1080/02656736.2018.1488004
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence of brain metastasis reduced by intra-operative hyperthermia treatment

Abstract: Purpose: Brain metastasis is a common complication in cancer patients. Local recurrence after total resection of metastatic brain tumor has been frequently reported. In this study, we developed a new hyperthermia device and applied it to metastatic brain tumor patients intra-operatively to study if hyperthermia treatment could reduce local tumor recurrence. Materials and methods: A total of 63 metastatic brain patients were enrolled in the study with an informed consent obtained from every patient. After total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Some studies have also shown that hyperthermia can enhance the immune attack on tumors (Frey et al, 2012). Studies have shown that postoperative hyperthermia can reduce local recurrence of brain metastases (Byun et al, 2018). HIPEC has traditionally been used for the treatment of peritoneal cancer and in combination with tumor Cell Reduction Surgery (CRS).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have also shown that hyperthermia can enhance the immune attack on tumors (Frey et al, 2012). Studies have shown that postoperative hyperthermia can reduce local recurrence of brain metastases (Byun et al, 2018). HIPEC has traditionally been used for the treatment of peritoneal cancer and in combination with tumor Cell Reduction Surgery (CRS).…”
Section: Resultsmentioning
confidence: 99%
“…HT intracavitary devices have also been developed and reported in a phase I clinical trial [248]. This devise is comprised of a water pump that circulates hot water to a cavitated gold coated sphere.…”
Section: Novel Ht Modalities In Clinical Settingsmentioning
confidence: 99%
“…Design HT modality Brain tumor type Byun et al [248] Clinical Novel hyperthermia device BM Schooneveldt et al [247] Clinical M/W PT Bredlau et al [244] Preclinical R/F Canines with no tumors Rozumenko et al [249] Clinical LSTT HGGs Roussakow SV, 2017 [246] Clinical EHT HGGs Cha et al [243] Preclinical EHT Human GBM (U87-MG þ A172) Man et al [32] Preclinical M/W Human GBM (patient derived glioma stem cells specimens 3691 and 387) Coluccia et al [237] Clinical U/S HGGs James et al [14] Preclinical R/F Rodent glioma (9L gliosarcoma) McDannold et al [236] Clinical U/S HGGs Wismeth et al [245] Clinical EHT HGGs Park et al [238] Clinical U/S HGGs HT: hyperthermia; R/F: radio-frequency hyperthermia; EHT: electro-hyperthermia; U/S: ultrasound; M/W: microwave hyperthermia; LSTT: laser surface thermal therapy; BM: brain metastasis; HGGs: high grade gliomas; PT: pediatric tumor.…”
Section: Studymentioning
confidence: 99%
“…[5]. При достижении температур 42−44 • C злокачественные клетки погибают, тогда как здоровые клетки не повреждаются [4][5][6][7]. МГТ лечение с использованием локализованных в опухоль МНЧ является одним из наиболее перспективных методов лечения агрессивного, разрушительного и не поддающегося лечению рака головного мозгаглиобластомы [8].…”
Section: Introductionunclassified